Pengaruh Investasi, Inflasi, dan Konsumsi Masyarakat Terhadap Pertumbuhan Ekonomi di Kota Surabaya - Achmad Albar Permana Suprianto; Wiwin Priana Primandhana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Economic growth is one of the benchmarks for assessing a country's economic development. A country that has an increase in continuous economic growth every year will advance development in that country. The purpose of this study was to determine the effect of investment, inflation, and public consumption on economic growth in the city of Surabaya. This study uses secondary data, namely time series data for 2011-2021. The analytical tool used in this study is multiple linear regression analysis using SPSS 25 software. The results show that partial investment has no effect on economic growth, inflation has a negative and significant effect on economic growth, and public consumption has a significant positive effect on economic growth in Surabaya cities. Keywords : Economic Growth, Economic Development, Investment, Inflation, Public Consumption.